Importance of the fatty acid chain length on in vitro and in vivo anticancer activity of fattigation-platform albumin nanoparticles in human colorectal cancer xenograft mice model - Park, Chulhun; Baek, Namhyun; Loebenberg, Raimar; Lee, Beom Jin (Journal of Controlled Release, 2020)
The aims of this study were to design different chain length fatty acid-conjugated albumin nanoparticles (ANPs) and evaluate their anticancer activity in the HCT116 human colorectal cancer xenograft mouse model. Doxorubicin hydrochloride (DOX·HCl) was chosen as a model drug. The different chain lengths of fatty acids (butyric acid; C4, and stearic acid; C18) in albumin conjugates exhibited different physicochemical properties and anticancer activity. Fatty acid-conjugated albumin aided the formation of self-assembled structures with an average size of approximately 200 nm and a negative charge when incubated with excess DOX in an aqueous solution. DOX-loaded long-chain C18-conjugated ANPs allowed efficient encapsulation of hydrophobic DOX into the core of the self-assembled structure, enabling higher drug loading, enhanced colloidal stability and controlled release behavior in PBS pH 7.4 medium as compared with free DOX·HCl or non-fatty acid conjugated ANPs. Furthermore, DOX-loaded fatty acid-conjugated ANPs showed an increased cellular uptake intensity and cytotoxic effects in vitro. In vivo, HCT116 xenograft model experiments confirmed that DOX-loaded C18-conjugated ANPs showed improved anticancer activity and reduced side effects compared with the DOX-treated groups. The long-chain fatty acid-conjugated ANPs synergistically activated the interaction with the free-fatty acid receptor (FFAR) on HCT116 colorectal cancer cells as compared with short-chain C4 or other non-conjugated ANPs. Specifically, DOX-loaded C18-conjugated NPs exhibited significant performance to overexpressed FFAR4 on HCT116 colorectal cancer cells. The fatty acid chain length in the fattigation-platform system could be a promising molecular moiety to improve targeting efficiency and drug accumulation in various cancer therapy.
Keywords: Albumin nanoparticles; Anticancer activities; Colloidal Stability; Colorectal cancer cell; Controlled release; Doxorubicin hydrochloride; Long chain fatty acid; Self assembled structures; Albumins; Animals; Colorectal Neoplasms; Doxorubicin; Drug Carriers; Drug Delivery Systems; Fatty Acids; Heterografts; Humans; Mice; Nanoparticles; Xenograft Model Antitumor Assays; Doxorubicin; Fattigation-platform; Fatty acid chain length; Fatty acid-conjugated albumin nanoparticles; HCT116 cancer cells; Human colorectal cancer xenograft mice model